(3GdeNJGQ ef efGbH GdCHQGQ heMGSf GdCNjGQs
(3ChdgG (B:s
(3Chd eGajg JQLeI GdaVd Hf YjGV s
(3Vef eLehY , JQJjHgG (B: (3ef U (B106 - (3U(B147s
(3JQGLe GdQLGd GdUhajIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdJGQjNs